Amendments to the Code of Canon Law in the years 1983-2022 - Adamowicz, Leszek (Prawo Kanoniczne, 2022)
Promulgated in 1983, the Code of Canon Law was amended many times by successive popes in the years 1983-2022. The article discusses the corrections of the promulgated text made by the legislator, and then the classic amendments to the code provisions changing the content of the canons. In addition to them, there were also "quiet" amendments "without changing the content of the canon", which de facto partly or entirely derogated from the existing regulations. The author also indicates which amendments were missing and which should be made to ensure the coherence of the canon law system. The amendments concerned six of the seven books of the Code of Canon Law, excluding only the fifth book. The sentence "Ecclesia semper reformanda" therefore also refers to canon law, which is a dynamic reality that must respond to new phenomena - both positive and negative - that take place in the community of the Church, which is a reality both holy and sinful. When analyzing the amendments made, one should also notice their imperfections, both substantive and affecting the legislative technique. It should be hoped, however, that the present times and the multiplicity and quality of changes made to the legal provisions of the Church will not cause disregard for the canon law that exists in the Church ad salutem animarum